The circular RNA aplacirc_13267 upregulates duck granulosa cell apoptosis by the apla‐miR‐1‐13/THBS1 signaling pathway. Issue 7 (22nd January 2020) - Wu, Yan; Xiao, Hongwei; Pi, Jinsong; Zhang, Hao; Pan, Ailuan; Pu, Yuejin; Liang, Zhenhua; Shen, Jie; Du, Jinping
Abstract: Follicle development is a key factor that determines the reproductive performance of poultry. The existing evidence suggests that circular RNAs (circRNAs) play an important role in a variety of biological processes, especially in posttranscriptional regulation, but the regulatory mechanism of circRNAs in duck follicle development has rarely been reported. To better explore the molecular mechanism of follicle development in ducks, we sequenced and analyzed the follicular circRNAs; 4, 204 circRNAs were predicted in the duck follicles. Fourteen circRNAs were differentially expressed between the white follicles and yellow follicles. The results of our studies showed that aplacirc_013267 promoted cell apoptosis in duck GCs. Moreover, a bioinformatics prediction analysis demonstrated that aplacirc_013267 was involved in a circRNA‐miRNA‐mRNA coexpression network and was observed to sponge two follicle‐related miRNAs by a luciferase activity assay. Furthermore, we found that overexpression of aplacirc_013267 significantly increased thrombospondin‐1 (THBS1) expression and downregulated granulosa cell apoptosis. The mechanistic study showed that aplacirc_013267 directly binds to and inhibits apla‐mir‐1‐13; then, aplacirc_013267 increases the expression of THBS1 and upregulates granulosa cell apoptosis. Taken together, our findings demonstrate that circRNAs have potential effects in duck ovarian follicles and that circRNAs may represent a new avenue to understand follicular development. Abstract : There were 14 circRNAs were differentially expressed between the white follicles and yellow follicles. The Circular RNA aplacirc_13267 upregulates duck granulosa cell apoptosis by apla‐miR‐1‐13/THBS1 signaling pathway. circRNAs have potential effects in duck ovarian follicles and that circRNAs may represent a new avenue to understand follicular development.